Behavioural Change of Individual Investors during the Financial Crisis - Cyril; George, Madhura (International Journal of Psychosocial Rehabilitation, 2020)
investment is the surplus money which one can capitalize in stocks, bonds, and real estate in anticipation of earning dividends or interest. Present consumption is sacrificed to get a return in the future. The sacrifice that has to be borne is certain but the return in the future may be uncertain. This attribute of investment indicates the risk factor. Investment has various attributes like time, quantity risk etc. However the most important attribute is the external environment which consists of economical market conditions, legal and political scenario of the place. This paper examines the process of investment decision-making in the context of financial crisis in a pioneering attempt to shed some light on crisis-induced changes in investment pattern by the individual investors. The objective is to study the kind of investments and riskiness of investment avenues during the financial crisis as considered by the various groups of individual investors. In addition, the study surveys the possible alternative avenues of investment for the individual investors when faced with crisis in the preferred portfolio. The study makes use of the statistical tools such as chi-square, correlation and paired sample test to test the hypotheses that are used in the study. In general, the study shows that financial crisis alters pattern of investment of the investors from the normal market conditions. The effect is more in the case of investors who invest in stock markets which mostly consists of self-employed investors. However, the majority of the individual investors prefer to invest in chit funds and bank deposits rather than other investment avenues. This research is based on the primary data collected through survey method. Besides I have taken few sights from various other secondary sources of data like journals, research articles magazines etc.